Faith-Based Leadership Integration: Applying Prophetic Values in Transformational and Servant Leadership for SME Entrepreneurs - Dikriyah; Muhammad Hariyadi; Suprihatin (UTSAHA: Journal of Entrepreneurship, 2026)
Leadership represents a critical determinant of entrepreneurial success and organizational sustainability, particularly within small and medium enterprises where ethical guidance directly influences stakeholder outcomes. This study analyzes the integration of Prophet Muhammad's leadership values within transformational and servant leadership models through systematic thematic Quranic exegesis. Employing qualitative descriptive methodology with tafsir maudhu'i approach, the research examines four key Quranic verses (Al-Imran 3:159, Al-Anbiya 21:107, Al-Furqan 25:63, and Al-Ma'idah 5:8) that articulate principles of consultative decision-making, visionary inspiration, humble conduct, and equitable justice. Findings reveal that prophetic leadership encompasses both transformational dimensions (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) and servant leadership characteristics (humility, empowerment, ethical behavior, and stewardship) within a unified theological framework. The analysis demonstrates that Quranic leadership principles challenge the artificial dichotomy between transformational vision-setting and servant stakeholder orientation prevalent in Western management scholarship, instead presenting an integrated paradigm termed "Quranic Leadership" that synthesizes change-oriented inspiration with humble ethical service. This framework offers Muslim entrepreneurs scripturally validated guidance for implementing evidence-based leadership practices while maintaining religious authenticity, contributing to faith-integrated entrepreneurship literature and providing practical implications for business educators, organizational leaders, and policymakers seeking culturally relevant approaches to ethical entrepreneurship and sustainable business development.